Two more new Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Tamil Nadu, India - Agarwal, Ishan; Bauer, Aaron M; Pal, Saunak; Srikanthan, Achyuthan N; Khandekar, Akshay (Zootaxa, 2020)
Two new species of the gekkonid genus Hemiphyllodactylus are described from mountains of the Western Ghats in Tamil Nadu, southern India. Hemiphyllodactylus nilgiriensis sp. nov. and H. peninsularis sp. nov. are > 5 % divergent in the mitochondrial ND2 gene from each other and members of the H. aurantiacus complex and differ from each other and members of the H. aurantiacus complex in several meristic characters and colouration. The description of these two new species takes the number of Indian Hemiphyllodactylus to six and the number of endemic geckos from Tamil Nadu to 15.